CLINICOPATHOLOGY OF PUPPY WITH ENTERITIS AND MYOCARDITIS DUE TO CANINE PARVOVIRUS INFECTION: A CASE REPORT - Sewoyo, Palagan Senopati; Winaya, Ida Bagus Oka; Berata, I Ketut; Adi, Anak Agung Ayu Mirah; Dayanti, Marissa Divia; Grahadi, Rahmat; Takariyanti, Dzikri Nurma'rifah (Buletin Veteriner Udayana, 2022)
Canine parvovirus (CPV) disease is a highly contagious disease in dogs, spread by the fecal-oral or oronasal route. This virus has a tropism in cells that are active and rapidly dividing. The animal used as the case study is a three months old local mixed breed male puppy from Denpasar, Bali. The case puppy was found to be sick for four days. Clinical examination showed the puppy had anorexia, depression, vomiting, bloody diarrhea, cough, fever, and dehydration. Polymerase chain reaction (PCR) assay showed the puppy was positive for CPV infection. The results of the routine hematological examination showed that the CPV-infected puppy had normochromic normocytic anemia, leukocytopenia, monocytosis, and neutropenia. The gross pathological changes observed were cerebral meninges hyperemia, lung hyperemia, epicardium necrosis, liver congestion, renal medulla hyperemia, and small intestine hyperemia. Histopathologically the changes observed were necrotizing myocarditis, emphysematous bronchopneumonia, hemorrhagic and necrotizing hepatitis, splenic lymphoid follicle depletion, renal glomerular atrophy, hemorrhagic and necrotizing enteritis, and hydropic degeneration of the urinary bladder transitional epithelium. Based on clinical symptoms, hematological examination, gross pathology, histopathology, as well as isolation and identification of the virus, it can be concluded that the puppy was infected with enteritis and myocarditis CPV concurrently.